Acute cardiac care in rheumatic mitral stenosis - Niazta, Nisa Amnifolia; Prasetya, Indra (Universitas Brawijaya, 2026)
Rheumatic heart disease (RHD) is prevented, although productive-age people may develop consequences. Indonesia, as an endemic country of RHD, predominantly reported isolated mitral stenosis among RHD patients. Acute worsening of mitral stenosis can lead to acute heart failure and cardiogenic shock, arrhythmias, stroke, pulmonary hypertension, systemic embolic events, infective endocarditis, and pregnancy-related issues. The diagnosis of critical valvular emergency, especially rheumatic mitral stenosis in acute cardiac care, is often overlooked due to the clinical history potentially resembling other disease entities. This review highlights clinical emergency manifestation and comprehensive management of rheumatic mitral stenosis in acute cardiac care.